Metode Maulang Kaji Pada Pembelajaran Santri Pondok Pesantren Nurul Yaqin Ringan-Ringan - Ilham, Muhammad Riski; Saputra, Edriagus; Movitaria, Mega Adyna; Delvia, Melda (Institut Agama Islam Sumatera Barat, 2023)
Pondok Pesantren Nurul Yaqin Ringan-ringan is a boarding school located in the Padang Pariaman Regency, Indonesia which has a lot of enthusiasts for students studying at the school. Apart from this, the school is famous for its Traditional Islamic Boarding Schools, there also has a learning method for its students that is unique and not shared by other schools in Indonesia, namely the Maulang Kaji Method. The method applied by the Nurul Yaqin Ringan-ringan Islamic boarding school has succeeded in providing a perfect understanding to all students in understanding the lessons carried out before learning will be taught by the teachers in the classroom. The purpose of this research is to reveal and understand the learning methods used by students at the Nurul Yaqin Ringan-ringan Islamic Boarding School, Padang Pariaman Regency. This research is a field research study using a qualitative descriptive analysis method. The results of this research can be concluded that the Maulang Kaji Method is a tradition that has been carried out from generation to generation by the students of the Nurul Yaqin Islamic Boarding School, Padang Pariaman, to prepare the lessons to be taught by the teachers. This was referred directly by the buya of the Islamic boarding school to the learning method of Imam Syafi'I who studied with Imam Malik. While the influence of the implementation of the maulang kaji method on learning for students, namely facilitating students in reading books, making it easier for students to understand learning material and students are more active in learning and discussion in the classroom, so that those who do not understand the material being taught, the students can ask without embarrassment.